Biofilm and dental unit waterline management. (2nd November 2021) - Yates, Laura
Abstract : Laura Yates discusses the problem of biofilm formation and management strategies to inhibit the growth of biofilms in DUWLs, to ensure water quality meets all required UK regulatory standards and to reduce potential risk factors for both patients and staff